Integrating NGS-derived mutational profiling in the diagnosis of multiple lung adenocarcinomas. (2021) - Ezer, Nicole; Wang, Hangjun; Corredor, Andrea Gomez; Fiset, Pierre Olivier; Baig, Ayesha; van Kempen, Léon C.; Chong, George; Issac, Marianne S.M.; Fraser, Richard; Spatz, Alan; Riviere, Jean-Baptiste; Broët, Philippe; et al.
Highlights: Distinguishing between MPLC and IPM is critical in lung oncology. A probabilistic model determined joint probability of mutations identified in 2 tumors. NGS results were most useful in cases of concordant mutations with low mutation frequency. Our series identified high incidence of KRAS and low incidence of EGFR mutations. Accuracy of diagnosis can be significantly improved with integration of NGS data. Abstract: MicroAbstract: Integration of Next Generation Sequencing (NGS) information for use in distinguishing between Multiple Primary Lung Cancer and intrapulmonary metastasis was evaluated. We used a probabilistic model, comprehensive histologic assessment and NGS to classify patients. Integrating NGS data confirmed initial diagnosis ( n = 41), revised the diagnosis ( n = 12), while resulted in non-informative data ( n = 8). Accuracy of diagnosis can be significantly improved with integration of NGS data. Background: Distinguishing between multiple primary lung cancers (MPLC) and intrapulmonary metastases (IPM) is challenging. The goal of this study was to evaluate how Next Generation Sequencing (NGS) information may be integrated in the diagnostic strategy. Patients and Methods: Patients with multiple lung adenocarcinomas were classified using both the comprehensive histologic assessment and NGS. We computed the joint probability of each pair having independent mutations by chance (thus being classified as MPLC). These probabilities were computed using the marginal mutation rates of each mutation, and the known negative dependencies between driver genes and different gene loci. With these NGS-driven data, cases were re-classified as MPLC or IPM. Results: We analyzed 61 patients with a total of 131 tumors. The most frequent mutation was KRAS (57.3%) which occured at a rate higher than expected ( p < 0.001) in lung cancer. No mutation was detected in 25/131 tumors (19.1%). Discordant molecular findings between tumor sites were found in 46 patients (75.4%); 11 patients (18.0%) had concordant molecular findings, and 4 patients (6.6%) had concordant molecular findings at 2 of the 3 sites. After integration of the NGS data, the initial diagnosis was confirmed for 41 patients (67.2%), the diagnosis was revised for 12 patients (19.7%) or was considered as non-informative for 8 patients (13.1%). Conclusion: Integrating the information of NGS data may significantly improve accuracy of diagnosis and staging.